Does residual microscopic disease after chemoradiotherapy for locally advanced rectal cancer translate into a good clinical outcome?. (March 2017) - Geva, R.; Davidovics, H.; Soyfer, S.; Pelles‐Avraham, S.; Klausner, J. M.; Inbar, M.; Tulchinsky, H.
Abstract: Aim: This study aimed to assess the progression‐free and overall survival of patients with residual microscopic disease following neoadjuvant chemoradiotherapy and rectal resection for locally advanced rectal cancer. Method: Two‐hundred and thirty‐four consecutive rectal cancer patients who had neoadjuvant chemoradiotherapy followed by radical resection (from May 2000 to April 2012) were divided according to pathological tumour response: residual microscopic disease (MIC), complete response (pCR) and partial/no response (non‐CR). Data on the neoadjuvant regime, treatment‐to‐surgery interval, final pathology, type of operation, operative time, postoperative complications, length of hospital stay, disease recurrence and mortality were compared between the groups. Results: There were 13 (5.5%) MIC patients, 48 (20.5%) with pCR and 173 (73.9%) with non‐CR group. The groups were demographically comparable. MIC patients had more retrieved lymph nodes compared with the non‐CR and pCR patients (median 13 compared with 8 and 10, respectively, P  =   0.0086). The 5‐year overall survival rates were 93.4% for the pCR and MIC patients vs 82.1% for the non‐CR patients ( P  =   0.0324). The 5‐year progression‐free survival was 85.2% for the pCR and MIC patients vs 73.8% for the non‐CR patients ( P  =   0.086). Conclusion: We have identified and assessed a new pathological subgroup of rectal cancer patients who had residual microscopic disease after neoadjuvant therapy. The survival analysis aligned them closely with pCR patients.